2021
DOI: 10.3390/ijms22126382
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Antioxidant Activity of Fullerenol C60,70 with Low Number of Oxygen Substituents

Abstract: Fullerene is a nanosized carbon structure with potential drug delivery applications. We studied the bioeffects of a water-soluble fullerene derivative, fullerenol, with 10-12 oxygen groups (F10-12); its structure was characterized by IR and XPS spectroscopy. A bioluminescent enzyme system was used to study toxic and antioxidant effects of F10-12 at the enzymatic level. Antioxidant characteristics of F10-12 were revealed in model solutions of organic and inorganic oxidizers. Low-concentration activation of biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 91 publications
5
22
1
Order By: Relevance
“…Humic substances, products of natural decomposition of organic matter in soils, coals, and bottom sediments, were the first bioactive compounds that we studied using this approach [49][50][51]. Later, the bioeffects of gold nanoparticles were analyzed in [52], the toxicity and antioxidant activity of a series of different fullerenol nanoparticles were evaluated and compared in [53][54][55][56][57][58][59], prooxidant properties of mignetide nanoparticles were demonstrated [60]. Thus, we have demonstrated that bacteria-based and enzyme-based bioluminescence assays exhibit strong potential as appropriate tools for studying and comparing the bioeffects of nanocompounds of different structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humic substances, products of natural decomposition of organic matter in soils, coals, and bottom sediments, were the first bioactive compounds that we studied using this approach [49][50][51]. Later, the bioeffects of gold nanoparticles were analyzed in [52], the toxicity and antioxidant activity of a series of different fullerenol nanoparticles were evaluated and compared in [53][54][55][56][57][58][59], prooxidant properties of mignetide nanoparticles were demonstrated [60]. Thus, we have demonstrated that bacteria-based and enzyme-based bioluminescence assays exhibit strong potential as appropriate tools for studying and comparing the bioeffects of nanocompounds of different structures.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant properties of bioactive compounds are supposed to be concerned with reactive oxygen species (ROS) in biological systems. The correlations between the ROS content and the toxic/antioxidant effects of bioactive compounds (fullerenols, gold nanoparticles, and radionuclides) in suspensions of luminous marine bacteria were studied in [52,53,59,[66][67][68][69]. The role of ROS in the toxic and antioxidant effects of endohedral Gd-containing fullerenols is of high interest; it has not been studied experimentally yet.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we began to use bioluminescence assays to evaluate the bioeffects of nanostructures of natural and artificial origin. We studied NPs with varied core material and surface modification [ 55 , 56 , 57 , 58 ]. Fullerene derivatives with diverse carbon cage sizes and oxygen substituent amounts, as well as core iron oxides, were under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we highlighted the involvement of the conjugated π-system of the carbon cage in fullerenol bioeffects [ 55 ]. We further demonstrated an active role of reactive oxygen species (ROS) in the bioeffects of fullerenol NPs [ 56 ]; ROS content was monitored using the chemiluminescence luminol method [ 59 , 60 ]. This technique determines integral ROS content by assuming a dynamic equilibrium of the different intra- and extracellular ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is characterized by the ability to accumulate in the tumour as it easily penetrates the permeable blood vessels that surround the neoplastic tissue [32]. To achieve increased water solubility and expand the possible biomedical applications, polar hydroxyl groups have been added to the C 60 skeleton [33]. Due to their specific structure that is characterized by the unique π-system, hydroxylated fullerenes are thought to have a dual nature.…”
Section: Introductionmentioning
confidence: 99%